Evaluation of Bay Leaf and Onion Peel Ethanolic Extracts for the Management of Kola Weevils (Balanogastris kolae) (Coleoptera: Curculionidae) in Stored Cola Nitida - Ibitoye, O.; Ogundare, A. O.; Ayangbemi, T. M.; Ogungbemi, K.; Oyewole, O. S.; Abel, O. O. (European Journal of Applied Sciences, 2022)
Farmers subject cured kolanuts to chemical treatment for control of kola weevils, kola nuts do not undergo any other additional form of post harvest processing before storage and consumption, therefore, there is an urgent need to develop new post harvest storage pest control strategies that are safe, of low cost, convenient to use, and environmentally / user friendly. The objective of the study is to assess the efficacy of Bay leaf and Onion peel ethanolic extracts on Balanogastris kolae against the chemical control measures. Efficacy of ethanolic extracts of Bay leaf and Onion Peels at concentrations of 20, 40, 60, 80 and 100 %v/v, each as protectant in the control of the Kola weevil Balanogastris kolae, were compared with a conventional insecticide, Cypermethrin at a rate of 5 ml / 100g Kolanut. Parameters evaluated include adult mortality, rate of adult emergence and nut damage which were subjected to analysis of variance and means between treatments were separated using LSD. Mortality of Balanogastris kolae increased with increasing concentration of the extracts as well as days of exposure, All the treatments were better than the control (P < 0.05) in reducing the number of emerged adult B. kolae and grain damage. All treatments proved superior to control (58.0%) with Cypermethrin and 90 %v/v Onion peel outstanding.